Comparative Evaluation of the Intranasal Spray Formulation of Midazolam and Dexmedetomidine in Patients Undergoing Surgical Removal of Impacted Mandibular Third Molars: A Split Mouth Prospective Study - Hiwarkar, Shashank (J Maxillofac Oral Surg, 2016)
PURPOSE: The purpose of this prospective randomized single blinded split mouth study was to conduct a comparative evaluation of the efficacy of intranasal atomised spray formulation of Dexmedetomidine with Midazolam in patients undergoing surgical removal of bilaterally impacted mandibular third molars. METHODS: This prospective study was conducted in twenty volunteers. Each volunteer underwent the surgical removal of an impacted mandibular third molar at two separate appointments at an interval of two weeks. The first third molar surgery was conducted using either intranasal Midazolam (Group M) or intranasal Dexmedetomidine (Group D). At the second appointment the surgical procedure was performed using the sedative agent not used at the first appointment. The primary testing outcome variables were Plasma oxygen saturation (SpO2), pulse and blood pressure and Modified Observer’s Assessment of Alertness/Sedation (OAA/S) scale. These were recorded at predetermined intervals starting 10 min before the administration of local anaesthesia and continued up to 10 min after completion of the procedure. In addition surgeon’s opinion regarding the patient cooperation, event amnesia, post operative nausea & vomiting were obtained. RESULTS: The sample composed of twenty patients (M = 9 and F = 11). There was statistically no significant difference between Group M and Group D with respect to mean SpO2. Minor differences were however noted at 20 and 30 min after sedation. There was no significant difference between the groups with respect to mean pulse rate, blood pressure, OAA/S, event amnesia, post operative nausea and vomiting and patient cooperation. CONCLUSION: We conclude that Midazolam and Dexmedetomidine are equivalent and can be used in minor oral surgery with minimal complications. These drugs can be used intranasally using nasal atomization device in routine outpatient basis in otherwise normal healthy but anxious patients. All procedures must however be performed in the presence of an anaesthesiologist and with ready availability of emergency drugs and equipment.